Pogostnost in raznolikost večstavčnih povedi v italijanskih neknjiževnih besedilih - Mertelj, Darja (Vestnik za tuje jezike, 2009)
Although it might seem that syntactically complex clauses rarely appear in everyday language and/or belong to higher language, they are also used in the context of a less demanding and less controlled verbal communication environment. The aim of this paper is to present their syntactically heterogeneous nature in some representative Italian texts, along with potential difficulties Slovenian learners may have when dealing with them. The analysis focuses on subordinate clauses introduced by the conjunctions se, anche se and come se which can introduce various subordinate clauses, most being notorious for Slovenian (and other Slavic) learners. Interference errors occur constantly, in particular as far as the appropriate use of verbal forms is concerned. It was found that all the subordinates in question appear in Italian text constantly, but they are not extremely common; their use is also not correlated to the type of text involved, but to the writer/speaker's communication goals. Due to their sporadic appearance and highly heterogeneous nature, they cannot represent a stable input for learners in order to enable their successful unconscious acquisition. That is why at least the prototypical usage of syntactic patterns should be included in the conscious learning of Italian as a foreign language despite their reduced importance attributed by recent tendencies in the field of foreign language methodologies.
Keywords: Italian; italijanščina; tuji jeziki; skladnja; syntax; sintaksa; večstavčne povedi; neknjiževna besedila; neliterarna besedila; didactic method; didaktika; metodika